If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -32 + -4x = 46 + -1x Solving -32 + -4x = 46 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. -32 + -4x + x = 46 + -1x + x Combine like terms: -4x + x = -3x -32 + -3x = 46 + -1x + x Combine like terms: -1x + x = 0 -32 + -3x = 46 + 0 -32 + -3x = 46 Add '32' to each side of the equation. -32 + 32 + -3x = 46 + 32 Combine like terms: -32 + 32 = 0 0 + -3x = 46 + 32 -3x = 46 + 32 Combine like terms: 46 + 32 = 78 -3x = 78 Divide each side by '-3'. x = -26 Simplifying x = -26
| 2x-5=5-2 | | 5x-3(2x-10)=25 | | 34+03*2-25+5= | | z^2-(3+4i)z-1-5i=0 | | -46-(-28)= | | 78+n=3n-40 | | 5y-8=12x+4 | | 5y+24=y-8 | | 1.84g-8=0.28 | | 48=3.2x | | 4x+8-8x=32-4x | | 84+n=36-3n | | 3y-18=6 | | 7-1.5x=62.5 | | 4x-47=7x+22 | | 5+5+5+5+5=555 | | 7-1.5x=64 | | 4x-2x=7+13 | | 4a+3=3a+13 | | -6a+(-18)= | | 180=2X+5+3X-5 | | 2x+x+12.5=116 | | 6(u-1)=8u-8 | | solvey=x^2+23forx | | y=x^2+23forx | | n+28=-112 | | 17b=1 | | 2x(3-5x)= | | 16/5=4u | | 21=7/3w | | (3y-1)(4y+7)= | | -1/2×-2-1 |